Perceptions of smokers influence nonsmoker attitudes and preferences for interactions. Issue 4 (18th March 2013) - Dillard, Amanda J.; Magnan, Renee E.; Köblitz, Amber R.; McCaul, Kevin D.
Abstract In two studies, we examined nonsmokers' perceptions of smokers and consequences of the perceptions. In Study 1, smokers answered questions about their sense of self, dependence on smoking, and motivation to quit. Nonsmokers answered questions about their perceptions of these characteristics. Differences between smokers' self‐descriptions and nonsmokers' perceptions were observed. Study 2 asked nonsmokers to judge two types of smokers for which the descriptions were based on Study 1 findings. Results showed that nonsmokers held a more negative attitude about and were less willing to engage in different close relationships with the smoker who was described in terms of nonsmokers' perceptions rather than smokers' reports. Attitude mediated the relationship between type of smoker and willingness to date a smoker.